Comparing Outcomes of Phacoemulsification and Endocyclophotocoagulation with Either Dual Blade Goniotomy (PEcK) or Two Trabecular Stents (ICE2) - El Helwe H; Oberfeld B; Golsoorat Pahlaviani F; Falah H; Trzcinski J; Solá-Del Valle D (Clinical Ophthalmology, 2023)
Hani El Helwe, Blake Oberfeld, Fatemeh Golsoorat Pahlaviani, Henisk Falah, Jonathan Trzcinski, David Solá-Del Valle Department of Ophthalmology, Harvard Medical School and Mass Eye and Ear, Boston, MA, USACorrespondence: David Solá-Del Valle, Massachusetts Eye and Ear, Harvard Medical School, 243 Charles Street, Boston, MA, 02114, USA, Email david_sola-delvalle@meei.harvard.eduPurpose: To compare outcomes of phacoemulsification and endocyclophotocoagulation with either dual blade goniotomy (PEcK) or two trabecular stents (ICE2).Setting: Retrospective, nonrandomized comparative study from a level 3 triage center.Methods: One hundred and seventy charts and a total of 1294 visits were reviewed following either PEcK or ICE2 from 2018 to 2022. One hundred and twenty-eight patients had PEcK and 42 underwent ICE2. Patients with less than 30 days of follow-up were excluded. The mean follow-up time was 505 ± 308 days. Two Kaplan–Meier curves (KM) assessed survival with ≤ baseline medications while maintaining (1) [GIC – Goal IOP Criteria] IOP ≤ goal IOP or (2) [PRC – Percent Reduction Criteria] IOP reduction ≥ 20% with 5 mmHg ≤ IOP ≤ 21 mmHg for at least two consecutive visits. IOP and medication burden reduction were compared using a paired t-test.Results: Most patients were Caucasian (65%) and had mild-stage glaucoma (43%). The most common glaucoma type was primary open-angle glaucoma (58%). Average age was 72.2 years at the time of surgery. Mean preoperative IOP was 17.58 ± 4.98 mmHg on 3.00 ± 1.41 medications in PEcK and 15.36 ± 3.58 mmHg on 1.81 ± 1.11 medications in ICE2 (p = 0.015 for IOP; p < 0.001 for medications). Under GIC, the success rate was significantly higher in PEcK at POM6 (69% vs 46%, p < 0.001) and POY1 (63% vs 36%, p < 0.001). Under PRC, the success rate was significantly higher in PEcK at POM6 (73% vs 61%, p = 0.031) and POY1 (67% vs 50%, p = 0.028). Mean reductions at POY1 were 5.00 ± 4.31 mmHg on 1.35 ± 1.08 less medications after PEcK and 3.14 ± 2.83 mmHg on 1.01 ± 0.94 less medications after ICE2 (p < 0.001 at POY1 for IOP; p < 0.05 after POW6 for medications).Conclusion: Both PEcK and ICE2 reduce medication and IOP from baseline, with PEcK having more favorable GIC and PRC success rates and greater IOP and medication reduction at 1 year.Keywords: microinvasive glaucoma surgery, phacoemulsification, endocyclophotocoagulation, Kahook Dual Blade, iStent inject, surgical outcomes